Mitochondrial Fission Mediates Endothelial Inflammation. Issue 1 (July 2020) - Forrester, Steven J.; Preston, Kyle J.; Cooper, Hannah A.; Boyer, Michael J.; Escoto, Kathleen M.; Poltronetti, Anthony J.; Elliott, Katherine J.; Kuroda, Ryohei; Miyao, Masashi; Sesaki, Hiromi; Akiyama, Tomoko; Kimura, Yayoi; et al.
Abstract : Endothelial inflammation and mitochondrial dysfunction have been implicated in cardiovascular diseases, yet, a unifying mechanism tying them together remains limited. Mitochondrial dysfunction is frequently associated with mitochondrial fission/fragmentation mediated by the GTPase Drp1 (dynamin-related protein 1). Nuclear factor (NF)-κB, a master regulator of inflammation, is implicated in endothelial dysfunction and resultant complications. Here, we explore a causal relationship between mitochondrial fission and NF-κB activation in endothelial inflammatory responses. In cultured endothelial cells, TNF-α (tumor necrosis factor-α) or lipopolysaccharide induces mitochondrial fragmentation. Inhibition of Drp1 activity or expression suppresses mitochondrial fission, NF-κB activation, vascular cell adhesion molecule-1 induction, and leukocyte adhesion induced by these proinflammatory factors. Moreover, attenuations of inflammatory leukocyte adhesion were observed in Drp1 heterodeficient mice as well as endothelial Drp1 silenced mice. Intriguingly, inhibition of the canonical NF-κB signaling suppresses endothelial mitochondrial fission. Mechanistically, NF-κB p65/RelA seems to mediate inflammatory mitochondrial fission in endothelial cells. In addition, the classical anti-inflammatory drug, salicylate, seems to maintain mitochondrial fission/fusion balance against TNF-α via inhibition of NF-κB. In conclusion, our results suggest a previously unknown mechanism whereby the canonical NF-κB cascade and a mitochondrial fission pathway interdependently regulate endothelial inflammation. Abstract : Supplemental Digital Content is available in the text.